Left Ventricular Hypertrophy Is Associated With Increased Infarct Size and Decreased Myocardial Salvage in Patients With ST‐Segment Elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention. Issue 1 (January 2017) - Nepper‐Christensen, Lars; Lønborg, Jacob; Ahtarovski, Kiril Aleksov; Høfsten, Dan Eik; Kyhl, Kasper; Ghotbi, Adam Ali; Schoos, Mikkel Malby; Göransson, Christoffer; Bertelsen, Litten; Køber, Lars; Helqvist, Steffen; Pedersen, Frants; et al.
Abstract : Background: Approximately one third of patients with ST‐segment elevation myocardial infarction (STEMI) have left ventricular hypertrophy (LVH), which is associated with impaired outcome. However, the causal association between LVH and outcome in STEMI is unknown. We evaluated the association between LVH and: myocardial infarct size, area at risk, myocardial salvage, microvascular obstruction, left ventricular (LV) function (all determined by cardiac magnetic resonance [CMR]), and all‐cause mortality and readmission for heart failure in STEMI patients treated with primary percutaneous coronary intervention. Methods and Results: In this substudy of the DANAMI‐3 trial, 764 patients underwent CMR. LVH was defined by CMR and considered present if LV mass exceeded 77 (men) and 67 g/m 2 (women). One hundred seventy‐eight patients (24%) had LVH. LVH was associated with a larger final infarct size (15% [interquartile range IQR, 10–21] vs 9% [IQR, 3–17]; P <0.001) and smaller final myocardial salvage index (0.6 [IQR, 0.5–0.7] vs 0.7 [IQR, 0.5–0.9]; P <0.001). The LVH group had a higher incidence of microvascular obstruction (66% vs 45%; P <0.001) and lower final LV ejection fraction (LVEF; 53% [IQR, 47–60] vs 61% [IQR, 55–65]; P <0.001). In a Cox regression analysis, LVH was associated with a higher risk of all‐cause mortality and readmission for heart failure (hazard ratio 2.59 [95% CI, 1.38–4.90], P =0.003). The results remained statistically significant in multivariable models. Conclusions: LVH is independently associated with larger infarct size, less myocardial salvage, higher incidence of microvascular obstruction, lower LVEF, and a higher risk of all‐cause mortality and incidence of heart failure in STEMI patients treated with primary percutaneous coronary intervention. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01435408.